Focused Ultrasound Improves NK-92MI Cells Infiltration Into Tumors - Yang, Chaopin; Du, Meng; Yan, Fei; Chen, Zhiyi (Frontiers in Pharmacology, 2019)
The efficiency of natural killer (NK) cells, adoptively transferred, for treatment against solid tumors is hindered by their difficulty to enter tumors from the blood circulation as well as their inability to prolong viability in the absence of IL-2. Among different sources of NK cells, we used genetically modified NK-92MI cells, a suitable candidate which can release IL-2 to maintain their viability and overcome undesirable side effects caused by systemic administration of exogenous IL-2. In this study, we evaluated whether the combination of focused ultrasound (FUS) and microbubbles can improve adoptively NK-92MI cell infiltration into ovarian tumors through biodistribution, immunofluorescence, and flow cytometry. The treatment effects of using this strategy twice a week were explored. The potential molecular mechanism of FUS assisting NK cell therapy was also initially explored through evaluating the expression of ICAM1 and CX3CL1 by qRT-PCR. Our results indicated that FUS and microbubbles can improve NK-92MI cells’ infiltration into tumors, and the combination of FUS and NK-92MI cells had a better treatment effect compared to the PBS group, but not compared to the NK-92MI group. The qRT-PCR results also showed that CX3CL1 may be involved in the process of FUS-assisted NK cell infiltration. These results indicate that further optimization of the FUS-assisted strategy is still needed to achieve therapeutic benefit.